Antiulcerogenic activity of Alchornea castaneaefolia: Effects on sornatostatin, gastrin and prostaglandin - Hiruma-Lima, C. A.; Calvo, T. R.; Rodrigues, C. M.; Andrade, FDP; Vilegas, Wagner [UNESP]; Brito, ARMS (Elsevier B.V., 2006)
The hydroethanolic extract of the leaves (HEL) and bark (HEB) obtained from Alchornea castaneaefolia (Euphorbiaceae) were investigated for their ability to prevent ulceration of the gastric mucosa in animal models. HEL (500 and 1000 mg/kg) and HEB (1000 mg/kg) significantly reduced the gastric injuries induced by the combination of HCl/ethanol and lowered the severity of gastric damage formation induced by indomethacin/bethanechol in mice. Further investigation showed that HEL also inhibited formation of ulcers in mice submitted to stress and pylorus ligature, but HEL did not modify gastric juice parameters in Shay mice. HEL was also effective in promoting the healing process in chronic gastric ulcer induced by acetic acid in rats. An enriched flavonoidic fraction (EFF at dose of 100 mg/kg) obtained from HEL reduced gastric lesions induced by HCl/ethanol and indomethacin/bethanechol in mice. Although EFF did not modify the amount of free mucus production by gastric mucosa, it was able to increase prostaglandin production. When administered to rats submitted to ethanol-induced gastric lesions, EFF increased the somatostatin serum levels, while the gastrin serum levels were proportionally decreased. Phytochemical investigation on HEL and EFF led to the isolation of flavonoids glycosides as the main compounds, thus suggesting that these substances may be involved in the observed antiulcer activity. (c) 2005 Elsevier B.V.. All rights reserved.
Keywords: Alchornea castaneaefolia; antiulcer activity; flavonoids; euphorbiaceae